Sincere Cooperation, Respect for Democracy and EU Citizenship: Sufficient to Guarantee Scotland's Future in the European Union?. Issue 5 (18th July 2014) - Kenealy, Daniel; MacLennan, Stuart
Abstract The position of an independent Scotland within the European Union (EU) has recently been a subject of considerable debate. The European Commission has argued that any newly independent state formed from the territory of an existing Member State would require an Accession Treaty. This article critiques that official position and distinguishes between a set of claims that could be made on behalf of an independent Scottish state, and a set of claims that could be made on behalf of the citizens of an independent Scottish state vis‐à‐vis the EU. It argues that the general principles of the EU Treaties ought to govern how Scotland is treated, and that a new Accession Treaty is not necessary. Furthermore, notwithstanding the jurisprudence of the European Court of Justice (ECJ) in the area of EU citizenship, we conclude that EU citizenship itself is not sufficient to guarantee or generate membership of the EU.